The impact of the COVID-19 pandemic on pediatric developmental services: a cross-sectional study on overall burden and mental health status - Peter Borusiak; Yuliya Mazheika; Susanne Bauer; Edda Haberlandt; Ilona Krois; Christian Fricke; Liane Simon; Petra Beschoner; Lucia Jerg-Bretzke; Franziska Geiser; Nina Hiebel; Kerstin Weidner; et al. (BMC, 2022)
Abstract Background The COVID-19 outbreak has taken a heavy toll on the mental well-being of healthcare workers, even those who have not been directly involved in the care of acutely ill patients. The aims of this study were to identify the overall burden and mental health status of healthcare workers in pediatric developmental services under the influence of the COVID-19 pandemic, and to identify the risk and protective factors associated with mental health. Methods This cross-sectional web-based study was part of a large multicenter VOICE study conducted among employees ((neuro-)pediatricians, psychologists, speech therapists, occupational therapists, etc.) from various pediatric developmental services between June and July 2020. A total of 1291 questionnaires regarding overall burden, mental health status (depression, generalized anxiety disorder and emotional exhaustion) and risk and protective factors for mental health (working conditions, potential problems during the COVID-19 pandemic and psychological resources) were analyzed. Descriptive statistics and multiple linear regression were used for data analysis. Results A total of 44.5% (574/1291) participants felt a high or very high overall burden during the COVID-19 pandemic. Of all the participants, 14.6% (171/1173) reported clinically significant levels of depressive symptoms, 17.0% (199/1173) reported generalized anxiety disorder symptoms and 44.6% (532/1192) reported emotional exhaustion. Multiple linear regression analyses identified several common risk and protective factors for mental health status variables. The burden of an increase in the quantity of work, fear of work and fear of becoming infected showed the strongest negative associations, whereas psychological resources and sufficient relaxation in leisure time exhibited the strongest positive associations. Conclusion Employees who were not directly involved in the care of acutely ill patients were also exposed to considerable stress, some of which was not different from that experienced by professionals who were directly affected. These employees should not be lost sight of and must be offered appropriate support.